Management and legal regulations for the practice of precision and organic agriculture - Matveev Vladimir; Dikareva Varvara; Larkina Alfia (E3S Web of Conferences, 2020)
This study presents an integrated approach to managing a modern agricultural enterprise. New digital technologies used in agriculture make it possible to optimize the processes of land cultivation, sowing, calculation and application of fertilizers, as well as harvesting. Satellite positioning system (GPS), automated steering system, remote sensing, and geo-mapping used in the complex can significantly increase the productivity and profitability of agricultural industry.